A Model for Building Research Capacity and Infrastructure in Oncology: A Nursing Research Fellowship - Ann M Mazzella Ebstein; Margaret Barton-Burke; Kristen L Fessele (Elsevier, 2020)
Objective: This article describes how one comprehensive cancer center in the Northeast United States reorganized their nursing research fellowship (NRF) with the goals of engaging nurses in research processes, developing a culture of inquiry, building nursing research capacity, and sustaining infrastructures for facilitating high-quality, nurse-led oncology research studies. Methods: The basis for the curriculum, course work, and research practicum is derived from academic courses taught at the undergraduate, graduate, and doctoral levels. Evidence from the current literature, expertise of nurse-scientists, and feedback from former fellows provided the background for a fellowship model that included: (1) amending curriculum timeframes; (2) incorporating protected time; (3) improving access to resources; (4) enhancing the protection, data sharing, and accessibility of data; and (5) involving nurse-scientists as mentors and facilitators of research processes. These factors were incorporated over 3 years. Metrics included individual class and overall course evaluations and ongoing assessments. Results: In three cohorts from 2016 to 2019, a total of 21 nurses were accepted, and 18 (86%) nurses completed the NRF. In cohort 1 through cohort 3, 17 fellows presented their research findings internally, and a total of nine projects were presented at external forums. There were seven fellows whose manuscript submissions resulted in 21 journal publications. Of the 18 fellows, 15 (83%) conducted institutional review board-approved studies and three (17%) fellows developed studies involving one concept analysis and two systematic reviews. Conclusions: Utilizing technology, the fellowship improved access beyond the classroom setting. Improved application processes, the inclusion of protected time for nurses, and mentoring from nurse-scientists demonstrate a commitment to fostering a culture supporting new knowledge and innovation for improving patient care.